ANALISIS KUANTITAS DAN KUALITAS TENAGA KERJA PERBANKAN SYARIAH YANG TERDAMPAK DISRUPSI DIGITAL - Nur Melinda Lestari (Universitas Muhammadiyah Prof Dr Hamka, 2020)
The challenge for the industrial era 4.0 towards the industrial era 5.0 which is felt by humans is the loss of many skills that are usually carried out by humans who are transferred to technology. The transformation of banking services due to technological disruptions felt by the banking world, conventional services that have been carried out face-to-face have been replaced by technology, business activities and banking products can be said to be disrupted by the emergence of various finances. technology platforms, especially those engaged in P2P Lending and Payment. This can threaten human resources in the banking world if there is no solution and adaptive action taken by the bank so that banking human resources will still have a place according to their level of expertise. Interpreting from primary and secondary data sources, the result is that there has been a significant decrease in the quantity of banking human resources, but simultaneously the bank is reskilling to improve the quality of human resources to be ready to face changes in banking services. towards an excellent service digital banking system that still adheres to the principle of prudence. Keywords: Digital Services, Challenges of Islamic Banking